2015
DOI: 10.1166/sam.2015.2100
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Field Emission and Ammonia Gas Sensing Properties of Multiwalled Carbon Nanotube-Graphene Like Hybrid Films Deposited by Microwave Plasma Enhanced Chemical Vapor Deposition Technique

Abstract: This paper reports the direct deposition of multiwalled carbon nanotube (MWCNT)-graphene like hybrid films on nickel substrate using a 2.45 GHz microwave plasma enhanced chemical vapor deposition (MW PECVD) system in the temperature range of 500-700 C at 20 Torr pressure. The films have been characterized by Raman spectra, high resolution transmission electron microscope (HRTEM), scanning electron microscope, high resolution X-ray diffraction and contact angle measurement. Raman spectroscopy and HRTEM reveal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Moreover, for graphene, high growth energy can be reached via heating or high energy excitation and, therefore, involves high temperature (from 500 C to more than 1000 C) or methods such as electron irradiation in the electron cyclotron resonance, mass selected ion beam deposition, arc-discharge, and microwave plasma enhanced chemical vapor deposition. 23,[34][35][36][37][38][39][40][41] This demonstrates that the high energy state can promote the formation of graphene-like sheets. High-power pulsed power supply, exciting ions (near arc discharge) with very high power densities and ion energy, 42,43 could be used to prepare the graphene-like nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, for graphene, high growth energy can be reached via heating or high energy excitation and, therefore, involves high temperature (from 500 C to more than 1000 C) or methods such as electron irradiation in the electron cyclotron resonance, mass selected ion beam deposition, arc-discharge, and microwave plasma enhanced chemical vapor deposition. 23,[34][35][36][37][38][39][40][41] This demonstrates that the high energy state can promote the formation of graphene-like sheets. High-power pulsed power supply, exciting ions (near arc discharge) with very high power densities and ion energy, 42,43 could be used to prepare the graphene-like nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Another significant factor affecting performance of sensing device is humidity. A hydrophobic sensing material operating at room temperature was developed by depositing hybrid films of MWCNT/graphene on Ni substrate employing microwave plasma enhanced chemical vapour deposition in 500 o C -700 o C at 20 Torr pressure (149). For ammonia sensing, quick response and recovery time, 96 s were observed for film deposited at 700 o C. Additionally, hydrophobic surface of film enables gas sensing even in humid environment.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%
“…Earlier single step method to grow CNT rich hybrid material has been reported. 6,7 Nguyen et al 8 have synthesized CNT-graphene hybrid lms on Ni by the low vacuum annealing of cellulose acetate and showed that the hybrid lm exhibited the substantial improvement in the optoelectrical and eld emission properties compared to their individual counterpart. CNT has already been proven as a promising eld emitter.…”
Section: Introductionmentioning
confidence: 99%